Contrasting effects of urbanization and agriculture on surface temperature in eastern China. Issue 16 (31st August 2016) - Zhou, Decheng; Li, Dan; Sun, Ge; Zhang, Liangxia; Liu, Yongqiang; Hao, Lu
Abstract: The combined effect of urbanization and agriculture, two most pervasive land use activities, on the surface climate remains poorly understood. Using Moderate Resolution Imaging Spectroradiometer data over 2010–2015 and forests as reference, we showed that urbanization warmed the land surface temperature (LST), especially during the daytime and in growing seasons (maximized at 5.0 ± 2.0°C in May), whereas agriculture (dominated by double‐cropping system) cooled the LST in two growing seasons during the daytime and all the months but July during the nighttime in Jiangsu Province, eastern China. Collectively, they had insignificant effects on the LST during the day (−0.01°C) and cooled the LST by −0.6°C at night. We also found large geographic variations associated with their thermal effects, indicated by a warming tendency southward. These spatiotemporal patterns depend strongly on vegetation activity, evapotranspiration, surface albedo, and the background climate. Our results emphasize the great potential of agriculture in offsetting the heating effects caused by rapid urbanization in China. Key Points: The combined effect of urbanization and agriculture on surface temperature was studied in eastern China Agriculture offsets surface urban heat island effects with large seasonal and geographic variations Evapotranspiration, albedo, and the background climate control the thermal effects associated with urbanization and agriculture